2005
DOI: 10.1084/jem.20050911
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of DOCK2, a regulator of the actin cytoskeleton in lymphocytes, suppresses cardiac allograft rejection

Abstract: Allograft rejection is induced by graft tissue infiltration of alloreactive T cells that are activated mainly in secondary lymphoid organs of the host. DOCK2 plays a critical role in lymphocyte homing and immunological synapse formation by regulating the actin cytoskeleton, yet its role in the in vivo immune response remains unknown. We show here that DOCK2 deficiency enables long-term survival of cardiac allografts across a complete mismatch of the major histocompatibility complex molecules. In DOCK2-deficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 51 publications
0
40
0
Order By: Relevance
“…3B). These results suggest that DOCK2 deficiency suppresses Con A-induced hepatitis not only by reducing V␣14 NKT cells in the liver, but also by attenuating activation of conventional T cells (31,38).…”
Section: Dock2 ϫ/ϫ Mice Are Resistant To Con A-induced Hepatitismentioning
confidence: 79%
“…3B). These results suggest that DOCK2 deficiency suppresses Con A-induced hepatitis not only by reducing V␣14 NKT cells in the liver, but also by attenuating activation of conventional T cells (31,38).…”
Section: Dock2 ϫ/ϫ Mice Are Resistant To Con A-induced Hepatitismentioning
confidence: 79%
“…Dock2-deficient lymphocytes show greatly reduced entry, egress and interstitial motility in lymphoid and non-lymphoid tissues. In murine models of cardiac allograft rejection and diabetes, deletion of Dock2 in lymphocytes was found to be protective, pointing to a role for Dock2 in migration of pathogenic T cells (7, 8). Over the past decade, Dock2 has also been found to regulate a range of Rac-dependent functions in neutrophils, dendritic cells and NKT cells (9-12).…”
Section: Introductionmentioning
confidence: 99%
“…A knockout study against DOCK2 demonstrated the alternative role of DOCK2, regarding murine T-and B-cell motility [5] and control of the cardiac transplant rejection in mice [6]. The prominent roles of DOCK2, such as immune modulation associated with T cell differentiation [7; 8] and neutrophil chemotaxis [9; 10] were also disclosed.…”
Section: Introductionmentioning
confidence: 99%